Evaluation the Effects of Some Relevant Parameters on Elastic Modulus of Pumpkin Seed and Its Kernel - Mohammad Hossein Abbaspour-Fard; Rasool Khodabakhshian; Bagher Emadi; Hasan Sadrnia (International Journal of Biomaterials)
The elastic modulus of two varieties of Iranian pumpkin seed and its kernel (namely, Zaria and Gaboor) were evaluated as a function of size (large, medium, and small), loading rate (2, 5, 8, and 10 mm/min), and moisture content (4, 7.8, 14, and 20% d.b) under quasistatic compression loading. The results showed that elastic modulus of pumpkin seed and its kernel decreased with increasing moisture content and also increasing loading rate, for the varieties under study. The average modulus of elasticity of pumpkin seed from 68.86 to 46.65 Mpa and from 97.14 to 74.93 Mpa was obtained for moisture levels ranging from 4 to 20%, for Zaria and Gaboor varieties, respectively. The elastic modulus of pumpkin seed decreased from 73.55 to 43.04 Mpa and from 101.83 to 71.32 Mpa with increasing loading rate from 2 to 10 mm/min for Zaria and Gaboor varieties, respectively.